Natural Control of Crocidosema (Epinotia) aporema (Walsingham) (Lepidoptera: Tortricidae) by Parasitoids and Entomopathogenic Fungi in Lotus corniculatus and Glycine max - Ribeiro, Adela; Silva, Horacio; Castiglioni, Enrique; Bartaburu, Sebastián; Martínez, Juan José (Agrociencia Uruguay, 2015)
Crocidosema (Epinotia) aporema (Walsingham) (Lepidoptera: Tortricidae) damages forage-legumes and soybeans (Glycine max L.) in South America. In Uruguay, the use of chemical insecticides to control this species in soybeans has decreased in the past few years. During this period, the production system has undergone modifications, becoming increasingly agricultural with a predominance of this crop in the northwestern region of the country. Given this new scenario, it must be determined if the composition and efficiency of C. aporema natural enemies´ communities have experienced any changes. This information needs to be considered in management programs that address this pest. The objective of this study was to update the list of larvae parasitoids and entomopathogens attacking the larval stage of C. aporema in Uruguay, recording and quantifying their presence in Lotus corniculatus L. and soybeans (Glycine max L.). Samples were taken weekly for two years. The total mortality of larvae of C. aporema was low throughout the period. The natural enemies found were Zoophthora radicans (Entomophthorales), which had been reported earlier; a non-identified nematode; and the larval endoparasitoid Trathala sp. Cameron (Hymenoptera: Ichneumonidae), first record for C. aporema in soybeans in Uruguay.